A real-time lane changing and line changing algorithm for driving simulators based on virtual driver behavior. Issue 4 (1st November 2017) - Naseri, H; Nahvi, A; Karan, F Salimi Naneh
Abstract: Driving simulators have become an essential tool for driver safety training, research and development of real-time warning devices, and evaluation of liabilities after vehicle accidents. Although simulation hardware has made much progress, there are still a huge number of deficiencies in simulation software. In this paper, lane changing and line changing maneuvers for virtual vehicles are presented. The presented algorithm consists of two main procedures: decision making and maneuver. First, a virtual vehicle decides when to change its lane/line. Then, it chooses its target lane and considers whether there is a sufficient gap to maneuver. If both conditions are satisfied, the virtual vehicle begins the maneuver. The desired path of the maneuver is created and the virtual vehicle follows the path using a path-following algorithm. As the path is followed, a collision-avoiding algorithm prevents the virtual vehicle from crashing into other virtual vehicles. To validate the behavior of the virtual vehicles, a few lane change scenarios were tested on ten drivers. The behavior of these subjects was compared to that of the virtual vehicle drivers operating under similar conditions. The results show that the decision making and the path of the virtual vehicle drivers are similar to those of the subjects by 84%.